2019
DOI: 10.1097/md.0000000000014844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenytoin on serum levels of homocysteine, vitamin B12, folate in patients with epilepsy

Abstract: Background: To determine the influence of phenytoin (PHT) monotherapy on the serum levels of homocysteine (Hcy), folate and vitamin B12 in patients with epilepsy. Methods: Literature retrieval was performed through PubMed, Web of Science, Embase, Cochrane Library, Chinese Wanfang Data, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Database databases as of the end of March 2018. Pooled weighted mean difference (WMD) and 95% CIs were calculated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(66 reference statements)
0
5
0
1
Order By: Relevance
“…Higher folate levels have been determined in children with CP fed by tube compared to those feeding normally. However, a high risk of folate deficiency, which may cause an increase in homocysteine levels, has been reported in children with CP using antiepileptic drugs (13,23,24). Vitamin D levels are determined by assessing 25 OH vitamin D levels in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Higher folate levels have been determined in children with CP fed by tube compared to those feeding normally. However, a high risk of folate deficiency, which may cause an increase in homocysteine levels, has been reported in children with CP using antiepileptic drugs (13,23,24). Vitamin D levels are determined by assessing 25 OH vitamin D levels in serum.…”
Section: Discussionmentioning
confidence: 99%
“…PHT-PB (phenobarbital), carbamazepine (CBZ)-VPA, vigabatrin (VIG)-LTG, tiagabin (TGB)-VIG, gabapentin (GBP)-LTG and LTG-TPM (topiramate) [30][31][32]. However, 35% of still patients remain poor responders [33], which clearly indicates that additional mechanisms contribute to hyperexcitability and epileptogenesis. The gap in the therapeutic treatment of epilepsy prompted us to search for novel drug combinations targeting novel pathways.…”
Section: Discussionmentioning
confidence: 99%
“…An Antiepileptic Drug (AED) with the least effect on homocysteine metabolism, as well as minimal cognitive, mood, and behavioral complications, is preferred. Some studies showed classic AEDs such as phenytoin (13), phenobarbital ( 14), valproic acid (15), and carbamazepine (15) most probably could be associated with increased homocysteine levels. However, increased homocysteine levels may also be observed in patients treated with such new-generation AEDs as oxcarbazepine and topiramate (16).…”
Section: Discussionmentioning
confidence: 99%